Recalcitrant Macular Hole Closure by Autologous Retinal Transplant Using the Peripheral Retina - Yamada K (Dove Medical Press, 2020)
Keiko Yamada,1,2 Takatoshi Maeno,3 Shunji Kusaka,4 Jorge G Arroyo,2 Mitsunori Yamada5 1Department of Ophthalmology, Faculty of Medicine, Osaka University, Osaka, Japan; 2Department of Ophthalmology, Harvard University Beth Israel Deaconess Medical Center, Boston, MA, USA; 3Department of Ophthalmology, Toho University Sakura Medical Center, Chiba, Japan; 4Department of Ophthalmology, Faculty of Medicine, Kindai University, Osaka, Japan; 5Yamada Eye Clinic, Tokushima, JapanCorrespondence: Keiko Yamada Email meyamada@mb3.tcn.ne.jpPurpose: The peripheral adult human retina has been found to contain neuroepithelial stem cells. In this study, we examined the efficacy of an auto-transplant of peripheral retina into refractory macular holes (MH) from both anatomic and physiologic perspectives.Methods: The population consisted of four female patients aged 72, 82, 65 and 84 years (cases 1– 4, respectively) with persistent refractory MH status; internal limiting membrane (ILM) peeling (case 1), ILM transplant (case 2), and inverted ILM (cases 3 and 4 with myopic MH). In all our cases, retinal grafts were harvested beyond the equator from the far retinal periphery using curved horizontal scissors and gently moved toward the MH using a forceps. A 25-G manipulator with a silicone ball tip was used to tuck the trimmed graft into the MH, followed by fluid-air exchange and infusion of silicone oil, which was removed three months later.Results: Partial restoration and integration of the outer retinal layer were confirmed on an OCT-B scan imaging. The visual acuity (VA) was improved in all cases: 1.2 to 1.0 logMAR (case 1), 2.0 to 1.3 logMAR (case 2), 2.3 to 1.4 logMAR (case 3) and 2.0 to 1.0 logMAR (case 4). Microperimetry showed improved retinal sensitivity in every case. No intra- or post-operative complications were observed.Conclusion: Under pathological conditions, the Müller glia reportedly serves as a source of neuronal progenitor cells in regenerating retina, continuing to divide and migrate to the outer nuclear layer thus replacing lost photo-receptors. Although the histological findings remain unknown, the positive anatomic and physiologic outcomes of the auto-transplanted retinal flap in our series suggest that this technique may offer an effective option for treating recalcitrant MH. Further studies are warranted.Keywords: retina, macular hole, vitrectomy, stem cell, transplant; Müller glia